Norms in the lab: inexperienced versus experienced participants - Schmidt, Robert J.; Schwieren, Christiane; Sproten, Alec N. (Discussion paper series, 2019)
Using coordination games, we study whether social norm perception differs between inexperienced and experienced participants in economic laboratory experiments. We find substantial differences between the two groups, both regarding injunctive and descriptive social norms in the context of participation in lab experiments. By contrast, social norm perception for the context of daily life does not differ between the two groups. We therefore conclude that learning through experience is more important than selection effects for understanding differences between the two groups. We also conduct exploratory analyses on the relation between lab and field norms and find that behaving unsocial in an experiment is considered substantially more appropriate than in daily life. This appears inconsistent with the hypothesis that social preferences measured in lab experiments are inflated and indicates a distinction between revealed social preferences as measured commonly and the elicitation of normatively appropriate behavior.